Toward Equitable Innovation in Health and Medicine: A Framework - National Academies of Sciences, Engineering, and Medicine; National Academy of Medicine (The National Academies Press, 2023)
Advances in biomedical science, data science, engineering, and technology are leading to high-pace innovation with potential to transform health and medicine. These innovations simultaneously raise important ethical and social issues, including how to fairly distribute their benefits and risks. The National Academies of Sciences, Engineering, and Medicine, in collaboration with the National Academy of Medicine, established the Committee on Creating a Framework for Emerging Science, Technology, and Innovation in Health and Medicine to provide leadership and engage broad communities in developing a framework for aligning the development and use of transformative technologies with ethical and equitable principles. The committees resulting report describes a governance framework for decisions throughout the innovation life cycle to advance equitable innovation and support an ecosystem that is more responsive to the needs of a broader range of individuals and is better able to recognize and address inequities as they arise.
Keywords: Health and Medicine

Discussion Draft of the Preliminary Framework for Equitable Allocation of COVID-19 Vaccine - National Academy of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On September 1, 2020, the National Academies of Sciences, Engineering, and Medicine invited public comment on the Discussion Draft of the Preliminary Framework for Equitable Allocation of COVID-19 Vaccine, commissioned by the Centers for Disease Control and the National Institutes of Health. Input from the public, especially communities disproportionately affected by the COVID-19 pandemic, is essential to produce a final report that is objective, balanced, and inclusive. The public comment period was open for 4 days, from 12:00 p.m. ET on Tuesday, September 1, until 11:59 p.m. ET on Friday, September 4. In addition, the study committee hosted a listening session on Wednesday, September 2, from 12:00 to 5:00 p.m. ET to hear comments from the public. For more information, please visit the study webpage. If you have any questions, please email COVIDVaccineFramework@nas.edu.
Keywords: Health and Medicine

The Neglected Dimension of Global Security: A Framework to Counter Infectious Disease Crises (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak.
Keywords: Health and Medicine; Conflict and Security Issues

Optimizing Strategies for Clinical Decision Support: Summary of a Meeting Series - National Academy of Medicine (The National Academies Press, 2017)
As a result of a collaboration between the National Academy of Medicine (NAM) and the Office of the National Coordinator for Health Information Technology, this NAM Special Publication summarizes and builds on a meeting series in which a multi-stakeholder group of experts discussed the potential of clinical decision support (CDS) to transform care delivery by ameliorating the burden that expanding clinical knowledge and care and choice complexity place on the finite time and attention of clinicians, patients, and members of the care team. This summary also includes highlights from discussions to address the barriers to realizing the full benefits of CDS-facilitated value improvement. Optimizing Strategies for Clinical Decision Support identifies the need for a continuously learning health system driven by the seamless and rapid generation, processing, and practical application of the best available evidence for clinical decision making and lays out a series of actionable collaborative next steps to optimize strategies for adoption and use of CDS.
Keywords: Health and Medicine

Perspectives on Health Equity and Social Determinants of Health - National Academy of Medicine (The National Academies Press, 2017)
Social factors, signals, and biases shape the health of our nation. Racism and poverty manifest in unequal social, environmental, and economic conditions, resulting in deep-rooted health disparities that carry over from generation to generation. In Perspectives on Health Equity and Social Determinants of Health, authors call for collective action across sectors to reverse the debilitating and often lethal consequences of health inequity. This edited volume of discussion papers provides recommendations to advance the agenda to promote health equity for all. Organized by research approaches and policy implications, systems that perpetuate or ameliorate health disparities, and specific examples of ways in which health disparities manifest in communities of color, this Special Publication provides a stark look at how health and well-being are nurtured, protected, and preserved where people live, learn, work, and play. All of our nation’s institutions have important roles to play even if they do not think of their purpose as fundamentally linked to health and well-being. The rich discussions found throughout Perspectives on Health Equity and Social Determinants of Health make way for the translation of policies and actions to improve health and health equity for all citizens of our society. The major health problems of our time cannot be solved by health care alone. They cannot be solved by public health alone. Collective action is needed, and it is needed now.
Keywords: Health and Medicine

Valuing America's Health: Aligning Financing to Reward Better Health and Well-Being - National Academy of Medicine (The National Academies Press, 2024)
The United States is experiencing a decline in life expectancy despite high health care spending due to a multitude of factors, including the COVID-19 pandemic, opioid epidemic, high burden of chronic disease, and systemic and structural inequities.A response proportional to this crisis is required. Valuing America's Health: Aligning Financing to Reward Better Health and Well-Being explores opportunities to transform the current health and health care system to one that promotes whole person and whole population health. The publication emphasizes the need for a bold vision and sustainable financing strategies to prioritize health and well-being for all. Authors of the publication highlight the importance of building a movement to prioritize health, repairing systemic failures, holding stakeholders accountable, controlling health care costs, incentivizing health promotion, adopting collaborative financing and policy-making approaches, and empowering individuals and communities in health decision-making.The way is clear; what is needed now is the will to move forward. Learn more about how to ensure our nation's health and health care system can support optimal health for all.
Keywords: Health and Medicine

International Workshop on COVID-19 Lessons to Inform Pandemic Influenza Response: Proceedings of a Workshop - National Academy of Medicine (The National Academies Press, 2022)
While the world continues to respond to the COVID-19 pandemic, novel influenza viruses persist as a constant pandemic threat. The global response to COVID-19 has pushed the boundaries on what is possible for rapid pandemic response in several areas, including vaccine research, development, manufacturing, equitable distribution, allocation, and administration. If well understood and sufficiently adapted, these actions could be applied to future pandemic and seasonal influenza vaccine preparedness efforts. However, developing and delivering these more effective vaccines to meet the demand goes beyond simply technical challenges and includes issues across governance, financing, research, supply chain, and public engagement. To address these challenges, the National Academies of Sciences, Engineering, and Medicine convened a virtual public workshop in May of 2021 to discuss the emerging evidence on unprecedented actions related to COVID-19 that could inform and advance pandemic and seasonal influenza vaccine preparedness efforts and subsequent response. This Proceedings of a Workshop provides a high-level summary of the presentations and discussions that occurred during the workshop.
Keywords: Health and Medicine

Emerging Stronger from COVID-19: Priorities for Health System Transformation - National Academy of Medicine (The National Academies Press, 2023)
In mid-2022, the United States has lost more than 1 million people to the COVID-19 pandemic. We have been real-time witnesses to scores of heroic responses to the disease, death, inequity, and economic strife unleashed by the virus, but have also experienced the consequences of poor pandemic preparedness and long-standing structural failures in our health system. For decades, the U.S. health system has fallen far short of its potential to support and improve individual and population health. The COVID-19 pandemic has presented death and devastation—but also an unprecedented opportunity to truly transform U.S. health, health care, and health delivery. To capitalize on this opportunity, the National Academy of Medicine gathered field leaders from across all of the major health system sectors to assess how each sector has responded to the pandemic and the opportunities that exist for health system transformation. The opportunity is now to capitalize on the hard-won lessons of COVID-19 and build a health care system that centers patients, families, and communities; cares for clinicians; supports care systems, public health, and biomedical research to perform at the best of their abilities; applies innovations from digital health and quality, safety, and standards organizations; and encourages health care payers and health product manufacturers and innovators to produce products that benefit all.
Keywords: Health and Medicine

Effective Care for High-Need Patients: Opportunities for Improving Outcomes, Value, and Health - National Academy of Medicine (The National Academies Press, 2017)
To advance insights and perspectives on how to better manage the care of the high-need patient population, the National Academy of Medicine, with guidance from an expert planning committee, was tasked with convening three workshops held between July 2015 and October 2016. The resulting special publication, Effective Care for High-Need Patients: Opportunities for Improving Outcomes, Value, and Health, summarizes the presentations, discussions, and relevant literature.
Keywords: Health and Medicine

Sharing Health Data: The Why, the Will, and the Way Forward - National Academy of Medicine (The National Academies Press, 2022)
Sharing health data and information across stakeholder groups is the bedrock of a learning health system. As data and information are increasingly combined across various sources, their generative value to transform health, health care, and health equity increases significantly. Health data have proven their centrality in guiding action to change the course of individual and population health, if properly stewarded and used. In the context of the COVID-19 pandemic, both data and a lack of data illuminated profound shortcomings that affected health care and health equity. Yet, a silver lining of the pandemic was a surge in collaboration among data holders in public health, health care, and technology firms, suggesting that an evolution in health data sharing is visible and tangible. This Special Publication features some of these novel data-sharing collaborations, and has been developed to provide practical context and implementation guidance that is critical to advancing the lessons learned identified in its parent NAM Special Publication, Health Data Sharing: Building a Foundation of Stakeholder Trust. The focus of this publication is to identify and describe exemplar groups to dispel the myth that sharing health data more broadly is impossible and illuminate the innovative approaches that are being taken to make progress in the current environment. It also serves as a resource for those waiting in the wings, showing how barriers were addressed and harvesting lessons and insights from those on the front lines. In the meantime, knowledge is already available to foster better health care and health outcomes. The examples described in this volume suggest how intentional attention to health data sharing can enable unparalleled advances, securing a healthier and more equitable future for all.
Keywords: Health and Medicine; Computers and Information Technology

Health Data Sharing to Support Better Outcomes: Building a Foundation of Stakeholder Trust - National Academy of Medicine (The National Academies Press, 2020)
The effective use of data is foundational to the concept of a learning health system—one that leverages and shares data to learn from every patient experience, and feeds the results back to clinicians, patients and families, and health care executives to transform health, health care, and health equity. More than ever, the American health care system is in a position to harness new technologies and new data sources to improve individual and population health.Learning health systems are driven by multiple stakeholders—patients, clinicians and clinical teams, health care organizations, academic institutions, government, industry, and payers. Each stakeholder group has its own sources of data, its own priorities, and its own goals and needs with respect to sharing that data. However, in America’s current health system, these stakeholders operate in silos without a clear understanding of the motivations and priorities of other groups. The three stakeholder working groups that served as the authors of this Special Publication identified many cultural, ethical, regulatory, and financial barriers to greater data sharing, linkage, and use. What emerged was the foundational role of trust in achieving the full vision of a learning health system.This Special Publication outlines a number of potentially valuable policy changes and actions that will help drive toward effective, efficient, and ethical data sharing, including more compelling and widespread communication efforts to improve awareness, understanding, and participation in data sharing. Achieving the vision of a learning health system will require eliminating the artificial boundaries that exist today among patient care, health system improvement, and research. Breaking down these barriers will require an unrelenting commitment across multiple stakeholders toward a shared goal of better, more equitable health.We can improve together by sharing and using data in ways that produce trust and respect. Patients and families deserve nothing less.
Keywords: Health and Medicine; Computers and Information Technology

Vital Directions for Health & Health Care: An Initiative of the National Academy of Medicine - National Academy of Medicine (The National Academies Press, 2017)
What can be more vital to each of us than our health? Yet, despite unprecedented health care spending, the U.S. health system is substantially underperforming, especially with respect to what should be possible, given current knowledge. Although the United States is currently devoting 18% of its Gross Domestic Product to delivering medical care—more than $3 trillion annually and nearly double the expenditure of other advanced industrialized countries—the U.S. health system ranked only 37 in performance in a World Health Organization assessment of member nations. In Vital Directions for Health & Health Care: An Initiative of the National Academy of Medicine, the National Academy of Medicine (NAM), which has long stood as the nation’s most trusted independent source of guidance in health, health care, and biomedical science, has marshaled the wisdom of more than 150 of the nation’s best researchers and health policy experts to assess opportunities for substantially improving the health and well-being of Americans, the quality of care delivered, and the contributions of science and technology. This publication identifies practical and affordable steps that can and must be taken across eight action and infrastructure priorities, ranging from paying for value and connecting care, to measuring what matters most and accelerating the capture of real-world evidence. Without obscuring the difficulty of the changes needed, in Vital Directions, the NAM offers an important blueprint and resource for health, policy, and leaders at all levels to achieve much better health outcomes at much lower cost.
Keywords: Health and Medicine

Procuring Interoperability: Achieving High-Quality, Connected, and Person-Centered Care - National Academy of Medicine (The National Academies Press, 2018)
Realizing the promise of digital technology will depend on the ability to share information across time and space from multiple devices, sources, systems, and organizations. The major barrier to progress is not technical; rather, it is in the failure of organizational demand and purchasing requirements. In contrast to many other industries, the purchasers of health care technologies have not marshaled their purchasing power to drive interoperability as a key requirement. Better procurement practices, supported by compatible interoperability platforms and architecture, will allow for better, safer patient care; reduced administrative workload for clinicians; protection from cybersecurity attacks; and significant financial savings across multiple markets.With funding support from the Gordon and Betty Moore Foundation, this National Academy of Medicine Special Publication represents a multi-stakeholder exploration of the path toward achieving large-scale interoperability through strategic acquisition of health information technology solutions and devices. In this publication, data exchanges over three environments are identified as critical to achieving interoperability: facility-to-facility (macro-tier); intra-facility (meso-tier); and at point-of-care (micro-tier). The publication further identifies the key characteristics of information exchange involved in health and health care, the nature of the requirements for functional interoperability in care processes, the mapping of those requirements into prevailing contracting practices, the specification of the steps necessary to achieve system-wide interoperability, and the proposal of a roadmap for using procurement specifications to engage those steps. The publication concludes with a series of checklists to be used by health care organizations and other stakeholders to accelerate progress in achieving system-wide interoperability.
Keywords: Health and Medicine

Catalyzing Innovative Health System Transformation: An Opportunity Agenda for the Center for Medicare & Medicaid Innovation - National Academy of Medicine (The National Academies Press, 2022)
Since its founding, the Center for Medicare & Medicaid Innovation (CMMI) has tested more than 50 alternative payment models reaching more than 28 million patients across 528,000 health care providers and plans, yielding invaluable insights on the implementation of models to achieve better care, better health, and lower costs. On the other hand, many basic lessons learned are lessons unapplied. U.S. population health outcomes lag behind its highly economically developed peers and our health system is still firmly entrenched in the fee-for-service payment system that rewards service volume. This Special Publication suggests six key priority actions for CMMI centered on signaling, mapping, measuring, modeling, partnering, and demonstrating. These priority actions, coupled with implementation considerations that focus on meaningful and continuous engagement, intersectionality and diversity, and expanding CMMI activities and impact, are intended to assist in aligning, supporting, and informing the implementation of CMMI’s Strategic Refresh.

First, Do No Harm: Marshaling Clinician Leadership to Counter the Opioid Epidemic - National Academy of Medicine (The National Academies Press, 2017)
There is no question that opioid use disorder has become the fastest growing, serious, and far-reaching public health crisis facing our nation today. The growing and unprecedented opioid epidemic is a critical issue for public health and medical care throughout the country. Provisional estimates suggest that nearly 65,000 Americans died from a drug overdose in 2016, a 21% increase from the previous year and at a level higher than occurred during the peak years for deaths from HIV infection and automobile fatalities.Nearly half of opioid overdose deaths are related to medications obtained legally by prescription, sparking deep concern among leaders in the health care sector. The need is clear for clinicians, as the "gatekeepers" of opioid prescriptions, and as the front line in facilitating access to treatment for addiction, to work together with state and community leaders to reduce the impact of opioid misuse on American communities.At the request of the National Governors Association, the National Academy of Medicine convened a group of experts and field leaders to explore clinicians' roles in addressing opioid misuse and addiction. The resulting Special Publication is informed by, and builds on, initiatives and guidelines that have been stewarded by various stakeholder organizations providing leadership in addressing these issues. In the midst of evolving understanding of and experience in pain management and substance abuse, the authors offer to clinicians a set of axioms applicable both to responsible, appropriate opioid prescribing practices, and to recognition and treatment of substance use disorder. Also underscored are actions that clinicians can take to improve their skills and effectiveness in the face of the growing need, including leadership engagement to ensure that communities have the resources and tools that clinicians require to fulfill their responsibilities.
Keywords: Health and Medicine

Artificial Intelligence in Health Care: The Hope, the Hype, the Promise, the Peril - National Academy of Medicine (The National Academies Press, 2019)
The emergence of artificial intelligence (AI) in health care offers unprecedented opportunities to improve patient and clinical team outcomes, reduce costs, and impact population health. While there have been a number of promising examples of AI applications in health care, it is imperative to proceed with caution or risk the potential of user disillusionment, another AI winter, or further exacerbation of existing health- and technology-driven disparities.This Special Publication synthesizes current knowledge to offer a reference document for relevant health care stakeholders. It outlines the current and near-term AI solutions; highlights the challenges, limitations, and best practices for AI development, adoption, and maintenance; offers an overview of the legal and regulatory landscape for AI tools designed for health care application; prioritizes the need for equity, inclusion, and a human rights lens for this work; and outlines key considerations for moving forward.AI is poised to make transformative and disruptive advances in health care, but it is prudent to balance the need for thoughtful, inclusive health care AI that plans for and actively manages and reduces potential unintended consequences, while not yielding to marketing hype and profit motives.
Keywords: Health and Medicine; Computers and Information Technology

National Plan for Health Workforce Well-Being - National Academy of Medicine (The National Academies Press, 2024)
In the United States, 54% of nurses and physicians, 60% of medical students and residents, and 61% of pharmacists have symptoms of burnout. Burnout is a long-standing issue and a fundamental barrier to professional well-being. It was further exacerbated by the COVID-19 pandemic. Health workers who find joy, fulfillment, and meaning in their work can engage on a deeper level with their patients, who are at the heart of health care. Thus, a thriving workforce is essential for delivering safe, high-quality, patient-centered care. The National Plan for Health Workforce Well-Being is intended to inspire collective action that focuses on changes needed across the health system and at the organizational level to improve the well-being of the health workforce. As a nation, we must redesign how health is delivered so that human connection is strengthened, health equity is achieved, and trust is restored. The National Plan’s vision is that patients are cared for by a health workforce that is thriving in an environment that fosters their well-being as they improve population health, enhance the care experience, reduce costs, and advance health equity; therefore, achieving the “quintuple aim.” Together, we can create a health system in which care is delivered joyfully and with meaning, by a committed team of all who work to advance health, in partnership with engaged patients and communities.
Keywords: Health and Medicine

Priorities on the Health Horizon: Informing PCORI's Strategic Plan - National Academy of Medicine (The National Academies Press, 2021)
In response to a growing national awareness that the development and use of new diagnostic, therapeutic, and preventive interventions had been occurring at a quickening pace—one far outstripping the evidence necessary to make informed decisions about their comparative advantage—the Patient-Centered Outcomes Research Institute (PCORI) was established in 2010 as part of the Affordable Care Act legislation. PCORI is guided by the imperative to help patients, families, clinicians, and other health care stakeholders make better informed health care decisions and improve care and outcomes. To inform the next steps in its organizational strategy, PCORI enlisted the National Academy of Medicine (NAM) to leverage its deep experience in convening experts on matters of significant national importance, including its long-standing thought leadership role in the realization of a learning health system. The NAM formed a multi-stakeholder workgroup and held two virtual convenings with the objective of engaging with patients, clinicians, health system leaders, researchers, and other stakeholders from the broader health community to identify and discuss high-priority emerging issues in health, health care, and biomedical science and technology. The key messages from these meetings are outlined in the Special Publication Priorities on the Health Horizon: Informing PCORI's Strategic Plan.Given the breadth of the domains considered in the Priorities on the Health Horizon meetings—emerging technologies, social and environmental factors, optimizing value, and infrastructure—a formidable set of pressing health and health care research needs were reviewed and discussed. In addition, certain fundamental strategic priorities emerged as basic and critical to progress in the field: (1) the need to reorient research perspectives and activities to patient and family priorities and values, and in particular, those conditions that drive inequities; (2) the need to foster strategic learning partnerships across groups, organizations, and sectors; and (3) the need to build the continuous learning infrastructure to produce new insights at the pace and scale necessary for health and health care improvement.Moving forward, building the capacity to continuously improve learning and sharing throughout the system will entail stakeholders working together as seamlessly as possible. The NAM and PCORI worked together to facilitate an expansive dialogue with key stakeholders and engender trust through a focus on shared commitments to progress on improving health for all Americans in the decade ahead.
Keywords: Health and Medicine

Caring for the Individual Patient: Understanding Heterogeneous Treatment Effects - National Academy of Medicine (The National Academies Press, 2019)
Evidence-based medicine arose from a clear need and represents a major advance in the science of clinical decision making. Despite broad acceptance of evidence-based medicine, however, a fundamental issue remains unresolved: evidence is derived from groups of people, yet medical decisions are made by and for individuals. Despite persistent assertions from clinicians that determining the best therapy for each patient is a more complicated endeavor than just picking the best treatment on average, traditional approaches have been overly reliant on the average effects estimated from the outcomes of clinical trials.This Special Publication is based on a workshop, held by the National Academy of Medicine, that considered patient and stakeholder perspectives on the importance of understanding heterogeneous treatment effects (HTE) and best practices for implementing clinical programs that take HTE into account. For evidence to be more applicable to individual patients, we need to combine methods for strong causal inference (first and foremost, randomization) with methods for prediction that permit inferences about which particular patients are likely to benefit and which are not. Better population-based outcomes will only be realized when we understand more completely how to treat patients as the unique individuals they are.
Keywords: Health and Medicine

Educating Together, Improving Together: Harmonizing Interprofessional Approaches to Address the Opioid Epidemic - National Academy of Medicine (The National Academies Press, 2021)
The United States is in the midst of an urgent and complex opioid crisis. To address how education and training can more effectively respond to this crisis, we must have a better understanding of problems in practice—or professional practice gaps—for health professionals and teams in practice. A coordinated response requires identifying and addressing professional practice gaps (PPGs) related to pain management, opioid use disorder, and other substance use disorder (SUD) care, as well as integrating evidence-based best practices into health professional education and training curricula across the continuum from undergraduate training into post-graduate continuing education This Special Publication presents two information-gathering efforts to assess persisting PPGs pertaining to pain management and SUD care and to better understand the current health professional education environment: the first is a comprehensive literature review, and the second is a survey of the regulatory landscape.The results underscore the need to collaboratively develop a harmonized interprofessional, person- and family-centered approach for the continuum of health professions education to more effectively address the opioid crisis.In this Special Publication, the Health Professional Education and Training Workgroup of the National Academy of Medicine’s Action Collaborative on Countering the U.S. Opioid Epidemic identified five action-oriented priorities to support this goal:Establish minimum core competencies in pain management and substance use disorders for all health care professionals, and support tracking of health care professionals’ competenceAlign accreditors' expectations for interprofessional collaboration in education for pain management and substance use disordersFoster interprofessional collaboration among licensing and certifying bodies to optimize regulatory approaches and outcomesUnleash the capacity for continuing education to meet health professions learners where they are through investment and leadership, andCollaborate to harmonize practice improvement initiativesWith due effort and support, these approaches will amplify effective practices while harmonizing and improving the environment for health care professionals to best serve the needs of their patients and communities.
Keywords: Health and Medicine